Hsa_circ_0005567 Activates Autophagy and Suppresses IL-1β-Induced Chondrocyte Apoptosis by Regulating miR-495 - Zhang, Jinling; Cheng, Fangyue; Rong, Genxiang; Tang, Zhi; Gui, Binjie (Frontiers in Molecular Biosciences, 2020)
Excessive chondrocyte apoptosis is mostly responsible for the progression of osteoarthritis (OA). It has been shown that circular RNAs (circRNAs) are differentially expressed in OA cartilage and participate in various pathological processes during OA. Here, this study was designed to explore the effect and molecular mechanism of hsa_circ_0005567 on IL-1β-induced chondrocyte apoptosis. The results showed that hsa_circ_0005567 knockdown aggravated the IL-1β-induced chondrocyte apoptosis. In contrast, hsa_circ_0005567 overexpression attenuated the IL-1β-induced chondrocyte apoptosis, but this effect could be abrogated by 3-methyladenine (an inhibitor of autophagy), suggesting that hsa_circ_0005567 overexpression inhibited chondrocyte apoptosis by inducing autophagy. Furthermore, hsa_circ_0005567 competitively bound to miR-495 and derepressed the expression of ATG14, an early autophagy marker was a direct target of miR-495. Moreover, both miR-495 mimic and ATG14 knockdown counteracted the autophagy-promoting and anti-apoptotic effects of hsa_circ_0005567 overexpression in IL-1β-treated chondrocytes. Taken together, hsa_circ_0005567 activates autophagy by regulating the miR-495/ATG14 axis and thereby suppresses IL-1β-induced chondrocyte apoptosis. These findings suggest that hsa_circ_0005567 may serve as a therapeutic target for the treatment of OA.